Respuesta :
The next one is add 7 since after you subtract x you would have -9 = 4x - 7
Answer:
Option 2 - Add 7
Step-by-step explanation:
Given : If the first step in the solution of the equation -9 + x = 5x - 7 is "subtract x,"
To find : What should the next step be?
Solution :
Expression [tex]-9 + x = 5x - 7[/tex]
Step 1 - Subtract x from both side,
[tex]-9 + x-x= 5x - 7-x[/tex]
[tex]-9= 4x - 7[/tex]
Step 2 - Add 7 both side,
[tex]-9+7= 4x - 7+7[/tex]
[tex]-2= 4x[/tex]
Step 3 - Solve,
[tex]x=\frac{-2}{4}[/tex]
[tex]x=-\frac{1}{2}[/tex]
So, The best next step is ''add 7 both side''
Therefore, Option 2 is correct.